PARTISIPASI DOSEN DALAM PENGAMBILAN KEPUTUSAN HASIL BELAJAR MAHASISWA - Sukirno DS (Universitas Negeri Yogyakarta, 1999)
The relationship beween particiption and marugeial performance has been ataaing not onty the business resmrchers bui also the educaional researchers. Nevenhclcss, represented for the topic of research has not consistmt conchsion and stiil limited in number, especialtv the education sectors. The purpose of tttis research vws to enpiricalty exanine the rehtionship between lecntrers panicipoion in decision making and pniciption satisfaction and srudmt otocomes in which organizption learning oppornnities and instnrctionar improvement gahered become intentening variobles. The needed were bt qucstionnaires. Lecturers who teach in accowuing The sCInptc of this research was coilcge depmnent in Dacrah Istimewa Yogyokarta. The samplz vns drawn by rtsing purposive technique- The resporce and utarsable rate were respeoivety (120 pieces) ord 5,a3 7o (7 pieces). The gathered'aou with regression, conel.ation arul path anatysis to te the research hypothesis. The results indicated that there are direct and indirect interaction betue.en rccturers prticipation satisfaction of the lecures on their on satdints'outcortcs.